Indikator Pemilihan Jurusan Pada SMK Nusantara menggunakan Metode SAW - Ulfatun Hasanah; Gunadi Widi Nurcahyo; Julius Santony (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
SMK Nusantara is one of the schools located in Bangko Sempurna District. This school annually conducts a selection of majors for its new students. The course is intended for students to complete the school according to their interests and abilities before continuing to the next level. The establishment of new student selection decision support system at SMK Nusantara using Simple Additive Weighting (SAW) method. Based on the information obtained from new admissions team, the number of departments that exist in SMK Nusantara consists of three departments, namely accounting, motorcycle engineering, and computer and networking techniques. The majors are based on the student's choice when enrolling by listing interest for majors 1 and department 2 otherwise the majors are determined by the value required in each department. By using simple additive weighting method is expected to help facilitate the acceptance of new students in determining the majors for each student. This decision support system is web-based so that it can be accessed anywhere by prospective students to register online, after that can be processed to determine the majors of each student. The results obtained in this settlement make it easier for new students to determine and access the majors to be chosen by their interests and talents. Research using this method get 100% result from 3 departments. 30% accounting for engineering, computer and network engineering 40%, and motorcycle technique 30%.